The Role of Parental Communication in Supporting the Achievement Needs of Children - Widya Salsabila; Maulana Rezi Ramadhana; Chairunnisa Widya Priastuty (PT Mattawang Mediatama Solution, 2024)
Parents have an important role in shaping personality and influencing a child's achievement, where this can start from communication between parents and children. Good communication supports increasing children's achievements, which automatically influences the children's needs and motivation. So, closeness and good interpersonal communication skills will be needed between children and their parents. This research aims to explore the role of parental communication in supporting children's achievement needs, especially at Pribadi High School Bandung. This research uses qualitative methods with a phenomenological approach to understand the experiences and views of research subjects. Data was collected through interviews with a number of students and parents at Bandung Private High School. Research findings show that the role of effective communication between parents and children in the aspects of openness, supporiveness and positiveness plays an important role in supporting children's academic achievements, increasing children's self-confidence and independence in achieving academic achievements. Additionally, this research found that parents who are actively involved in their child's education can provide significant emotional and moral support. Based on these findings, researchers recommend that parents pay attention to the quality of their communication with their children and create a supportive environment for their children's academic development.